Ericaceae endémicas del Perú - León, Blanca (2006)
The Ericaceae, a characteristic family of Peru´s montane forests, are represented in Peru by 22 genera and 132 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all of them perennial plants, from shrubs to climbing plants. Here we recognize 51 species and four varieties as Peruvian endemics in 14 genera. Thibaudia and Demosthenesia are the genera with the largest number of endemic species. Endemic Ericaceae are found in the Mesoandean and Very Humid Montane Forests regions, between 1000 and 3600 m elevation. Eleven of these endemic taxa have been collected to date within Peru´s protected areas system.